2002
DOI: 10.1097/01.asn.0000030142.80452.11
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Consequences of Vasopeptidase Inhibition in Humans

Abstract: Abstract. The in vivo inhibition of angiotensin-converting enzyme (ACE) and neutral endopeptidase (NEP) were monitored simultaneously by sequentially measuring the urinary excretion of N-Acetyl-Ser-Asp-Lys-Pro and of the atrial natriuretic factor to compare the magnitude and the duration of action of a vasopeptidase inhibitor, omapatrilat, and an ACE inhibitor, fosinopril. Single oral doses of 40 or 80 mg of omapatrilat or 20 mg of fosinopril were administered to 24 normotensive, sodiumdepleted or -replete vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
6
21
1
Order By: Relevance
“…4,5 For example, dual neprilysin-angiotensin converting enzyme inhibition was a logical combination from a pharmacological point of view, working by mutually reinforcing the effects of vasodilatory and natriuretic peptides (ANP and bradykinin) and decreasing the effects of vasoconstrictor and anti-natriuretic peptide (angiotensin II). 7,8 Indeed, the first representative of this class, omapatrilat, had a BP-lowering effect that would have been effective to treat patients with resistant hypertension. 8 However, the benefit/risk balance of this class of drugs was unfavourable.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For example, dual neprilysin-angiotensin converting enzyme inhibition was a logical combination from a pharmacological point of view, working by mutually reinforcing the effects of vasodilatory and natriuretic peptides (ANP and bradykinin) and decreasing the effects of vasoconstrictor and anti-natriuretic peptide (angiotensin II). 7,8 Indeed, the first representative of this class, omapatrilat, had a BP-lowering effect that would have been effective to treat patients with resistant hypertension. 8 However, the benefit/risk balance of this class of drugs was unfavourable.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of NEP should confer additional cardiovascular benefit by virtue of enhancing the hemodynamically favorable actions of the atrial natriuretic peptides, which are substrates for NEP (Robl et al, 1997;Burnett, 1999;Weber, 2001). Data from animal studies have indicated that the VPI omapatrilat does indeed confer greater cardiovascular benefit than ACE inhibitors alone (Trippodo et al, 1998;Bä cklund et al, 2001;Pu et al, 2002), and there is some data to suggest that this can also be seen in patients (Campese et al, 2001;Azizi et al, 2002;Ferrario et al, 2002). The development of omapatrilat, however, has been hampered by a 3-fold higher incidence of angioedema than observed with an ACEI (Coates, 2002;Campbell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…68 These higher doses of omapatrilat produced greater suppression of plasma ACE activity and greater stimulation of plasma renin levels than did fosinopril. At 24 hours after drug dosing, in comparison with fosinopril, these 2 doses of omapatrilat produced similar decreases in blood pressure in sodium-depleted subjects and greater decreases in blood pressure in sodium-supplemented subjects.…”
Section: Evaluation Of Vasopeptidase Inhibitors In Humans Normotensivmentioning
confidence: 91%
“…Omapatrilat, but not fosinopril, also produced increases in plasma levels of big endothelin, but no change in endothelin level. 68 Omapatrilat (40 mg and 80 mg) was also compared with fosinopril/hydrochlorothiazide combination (20 mg and 12.5 mg) in normotensive subjects. 69 Although the acute natriuretic effects of the fosinopril/hydrochlorothiazide combination were higher, the cumulative sodium excretion was similar for omapatrilat and the fosinopril/hydrochlorothiazide combination over 7 days.…”
Section: Evaluation Of Vasopeptidase Inhibitors In Humans Normotensivmentioning
confidence: 99%
See 1 more Smart Citation